Analisis Perankingan Supplier Bahan Baku Methanol Dengan Metode Fuzzy Analitycal Hierarchy Process (FAHP) Di PT XYZ - Tarissa Berliana Kartika; Dira Ernawati (Pusat Riset dan Inovasi Nasional, 2023)
This study uses the Fuzzy Analytical Hierarchy Process (FAHP) method to examine the choice of methanol raw material sources at PT XYZ. The procedure of gathering primary and secondary data for this study entails identifying supplier selection criteria, compiling data on criteria and sub-criteria, and compiling information on supplier performance. Results indicated that product quality, price, supply reliability, sustainability, and reputation were important factors in PT XYZ's decision to choose a certain supplier for its methanol raw materials. The relative weight of each criterion and sub-criteria has been computed using the FAHP approach, which aids in assessing possible providers. Additionally, depending on the obtained priority values, supplier rankings are also established. In conclusion, PT XYZ may choose its raw material suppliers for methanol using the FAHP approach effectively. As well as producing more objective and organized outcomes, this strategy aids in lowering decision-making uncertainty and complexity.